Severe cardiac dysfunction in a patient with multisystem inflammatory syndrome in children associated with COVID-19: Retrospective diagnosis of a puzzling presentation. A case report. (September 2020) - Vari, Daniel; Miller, Jonathan M.; Rellosa, Neil; Srivastava, Shubhika; Frizzola, Meg; Thacker, Deepika
Abstract: We report one of the earliest known U.S. cases of multisystem inflammatory syndrome in children associated with COVID-19 (MIS-C). This adolescent male presented prior to any known association between COVID-19 and immune mediated inflammatory syndrome in children. He presented in stable condition and without significant multisystem involvement. During hospitalization, he developed severe left ventricular dysfunction and mixed hypovolemic, distributive and cardiogenic shock. Clinical features overlapped with Kawasaki disease, acute rheumatic fever, and toxic shock syndrome. After centers in Europe began reporting a multisystem inflammatory condition in children with COVID-19, the patient's clinical course and laboratory findings were revisited. He underwent newly available antibody testing and was diagnosed as one of the first known cases of MIS-C in the United States.